Thinking Styles of Malay Undergraduates in a Malaysian Public University: A Case Study. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)
In embracing the challenges of a globalised world, individuals must possess a balanced thinking competency. They must have the inclination to use the right-brain to creatively produce new ideas and at the same time utilize the left-brain to increase their analytical and critical thinking skills.